Avaliação radiográfica da articulação coxofemoral em cães submetidos à exercícios físicos - Melo, Denise Gomes (2013)
In this study, the hip joints of six adult dogs of two breeds, from kennels belonging to the military police were radiographed in one year. To predict the influence of exercise on hip dysplasia, 259 radiographs of dysplastic dogs were reviewed in a retrospective study corresponding to a period of eight years trying to establish, among other variables, all types of radiographic lesions, were not routinely exposed to physical exercise. It can be concluded that the exercise was not a progress factor for dogs with hip dysplasia. If supervised, even when intense, exercise can be quite beneficial for hip joints.